Modifikasi Metode Bubble Aerator dan Filtrasi dalam Menurunkan Kadar TSS dan COD pada Limbah Cair Domestik di Jalan Pemuda Kota Tanjungpinang Tahun 2019 - Veronika Amelia Simbolon; Razor Armada; Rinaldi Daswito (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2019)
Domestic wastewater is wastewater, if not treated it can cause pollution. One of the efforts to reduce levels of Total Suspended Solid (TSS) and Chemical Oxygen Demand (COD) is to treat domestic waste. This study uses a modified bubble aerator and filtration method with zeolite, beach sand, and activated charcoal as an effort to reduce the levels of COD and TSS in domestic wastewater. This research method is a pre-trial using the One Group Pretest Postest design. Measurement of results is done before and after calculation. The sampling technique uses purposive sampling. Data analysis performed was univariate and bivariate analysis. Paired statistical t-test was used to find out the difference in average TSS and COD levels before completion. Decreased TSS levels after training (79.36%) and COD after administration (13.48%). Paired t test results showed no difference before and after using the bubble aerator and filtration modification methods with p values ​​of 0.342 and 0.448, respectively. Modifications to the bubble aerator and filtration methods can be used to reduce TSS and COD levels in domestic wastewater, although statistics show insignificant results. It is hoped that further researchers will conduct further research to perfect the methods that had been estimated. Keywords: TSS levels, COD, bubble-filtation aeration method